RANCANG BANGUN SISTEM INFORMASI POINT OF SALES PADA CAFE CALANDRA MENGGUNAKAN FRAMEWORK LARAVEL - Damara, Muhammad Zidane; Arribe, Edo; Risnen Nirwana (JURNAL ILMIAH INFORMATIKA, 2024)
The food and beverage (FnB) industry in Pekanbaru is experiencing a surge in popularity, marked by a proliferation of cafes and eateries. Amidst this competitive landscape, Calandra, an FnB establishment, faces the imperative to modernize its operations to stay ahead. This paper delves into the challenges confronted by Calandra amidst the technologically driven FnB environment and proposes the implementation of a Point of Sales (POS) System as a pivotal solution. Leveraging the Laravel framework and adhering to the Model, View, Controller (MVC) architecture, the envisioned POS system aims to revolutionize Calandra's operational landscape. Key objectives include the accurate recording of sales transactions, seamless integration for adding new menu items on their user website, enhancement of operational efficiency, and streamlining service processes. By meticulously designing and implementing this POS system, the authors envision it as an indispensable tool facilitating transactions with customers while providing comprehensive transaction history data. Through a detailed analysis of Calandra's operational dynamics and the proposed POS system's functionalities, this study offers insights into the transformative potential of technology in optimizing FnB businesses amidst a competitive market landscape.